Germ line BRCA1 & BRCA2 mutations in Greek breast/ovarian cancer families: 5382insC is the most frequent mutation observed - Ladopoulou,A.; Kroupis, C.; Konstantopoulou, I.; Ioannidou-Mouzaka,L.; Schofield,A.C.; Pantazidis,A.; Armaou,S.; Tsiagas,I.; Lianidou,E.; Efstathiou, E.; Tsionou,C.; Panopoulos, C.; et al. (Cancer Lett., 2002)
BRCA1 and BRCA2 genes were screened for loss-of-function mutations in a series of 85 patients having at least one first- or second-degree relative affected by breast and/or ovarian cancer. All BRCA1 exons and BRCA2 exons 10 and 11 were screened with a combination of methods including SSCP, PTT and direct sequencing. We have found disease-associated mutations in 14 families (16.5%), eleven in BRCA1 and three in BRCA2. The known founder mutation 5382insC of BRCA1 was identified in seven unrelated families. The other mutations identified include the non-sense R1751X, the splice junction variant 5586G>A of BRCA1 and three frameshifts, 2024del5, 3034del4, and 6631del5, of BRCA2. Nine out of these 14 families had a family history of three or more breast/ovarian cancer cases. A large number of polymorphic or unclassified variants is also reported. Combined with our previously published data 5382insC was found in nine out of 20 families (45%), suggesting that this mutation may represent a common founder mutation in the Greek population
Keywords: Adult; Breast Neoplasms; DNA Mutational Analysis; Epidemiology; Exons; Female; Genes,Brca1; Genes,Brca2; Genetic Testing; genetics; Germ-Line Mutation; Greece; Humans; Immunoenzyme Techniques; Introns; Male; metabolism; methods; Middle Aged; Ovarian Neoplasms; Pedigree; Polymorphism,Single-Stranded Conformational; Receptors,Estrogen